Utopia e antiutopia contemporânea: a utopia da cidadania planetária e a antiutopia da sociedade de consumo - Araújo, Rogério Bianchi de (2008)
The objective of this thesis is to problematize the role of utopia in contemporaneity without explaining all its nuances, nor to attempt to come up with an interpretation of utopia throughout various historical contexts. This thesis does not intend to be a conclusive study given the wealth of references on utopia, particularly in the area of study of Human Sciences. I am focussing on a part of an epistemological study, which permits us to think about contemporary utopia and anti-utopia from the perspective of some authors, whose ideas I will use with the purpose of bringing their thoughts together in a way that seems most appropriate to comprehend the role of utopia in contemporaneity. By analyzing some of Gianni Vattimo and Edgar Morin s works, I will discuss the necessity to create a new paradigm of thought, which permits us to reconnect to objectivity and subjectivity, which were lost after the Cartesian paradigm. Utopia is a development of ethics and principles, which guide utopian thought. It contains in itself an objectivity of thought which creates a dialogic relationship between the concrete possibilities of realization and the imaginary possibilities of day dreaming. Following this line of thought , I used, Ernst Bloch s Principle of Hope and Hans Jonas Principle of Responsibility as my references and in such a way that they would complement each other and not the contrary. In conclusion, I intend to demonstrate that the utopia of the development of a planetary citizenship is stimulated through the expansion of the consumer society, which I consider to be a contemporary anti-utopia. Some authors, such as Jean Baudrillard and Zygmunt Bauman are important references for problematizing the disastrous effects of the consumer society. I used various information sources, besides the authors cited, including references from cinema and literary works, which I used to justify my arguments given that utopia contains both objective and subjective dimensions of analysis. It is possible to affirm that in contemporaneity, it has not disappeared, rather, there are new paradigms that have emerged and this thesis seeks to discuss those